Gasification of Crop Residue Briquettes in an Open Core Down-draft Gasifier - Pareek, Devendra; Narnaware, Sunil; Joshi, Asim; Verma, Vikas K (Journal of Agricultural Engineering, 2011)
Gasification of crop residue briquettes was studied in an open core, throatless, down-draft gasifier of 1800 MJ.h?Â¹ capacity. Briquettes of 25, 35 and 55 mm diameters were prepared using sugarcane baggase, cotton stalk and ground nut shell, separately, in a piston press briquetting machine. Series of experiments were conducted to study performance of the gasifier in terms of fuel consumption rate, calorific value of producer gas and gasification efficiency using briquettes of selected crop residue. The performance was compared with the performance data already available for babul wood. The gasifier was found working satisfactorily with the babul wood and briquettes of all the three crop residues of three sizes. The gasification efficiency was highest for groundnut shell briquettes, followed by babul wood, sugarcane baggase briquettes and cotton stalk briquettes. The study revealed that clinker formation was lower and calorific value of the gas higher for gasification of smaller sized biomass briquettes.